2020
DOI: 10.1101/2020.12.03.20243683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Household factors and the risk of severe COVID-like illness early in the US pandemic

Abstract: ObjectiveTo investigate the role of children in the home and household crowding as risk factors for severe COVID-19 disease.MethodsWe used interview data from 6,831 U.S. adults screened for the Communities, Households and SARS/CoV-2 Epidemiology (CHASING) COVID Cohort Study in April 2020.ResultsIn logistic regression models, the adjusted odds ratio [aOR] of hospitalization due to COVID-19 for having (versus not having) children in the home was 10.5 (95% CI:5.7-19.1) among study participants living in multi-uni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Household transmission of SARS-CoV-2 occurs with very high attack rates, and may also increase the risk of more severe COVID-19 disease, requiring hospitalization. 23 Household crowding, more than population density, was shown to be a characteristic of community transmission ‘hotspots’ in a recent ecological analysis from the early phase of the pandemic. 24 When there are possible or confirmed cases of SARS-CoV-2 among household members, when background community transmission is substantial, or when the possibility of exposure outside the household is high (e.g., essential workers), our study and others 25 suggest mask use in the household should be considered, especially when it is otherwise not possible to limit potential exposure and spread in the household by isolating or sequestering away from others.…”
Section: Discussionmentioning
confidence: 99%
“…Household transmission of SARS-CoV-2 occurs with very high attack rates, and may also increase the risk of more severe COVID-19 disease, requiring hospitalization. 23 Household crowding, more than population density, was shown to be a characteristic of community transmission ‘hotspots’ in a recent ecological analysis from the early phase of the pandemic. 24 When there are possible or confirmed cases of SARS-CoV-2 among household members, when background community transmission is substantial, or when the possibility of exposure outside the household is high (e.g., essential workers), our study and others 25 suggest mask use in the household should be considered, especially when it is otherwise not possible to limit potential exposure and spread in the household by isolating or sequestering away from others.…”
Section: Discussionmentioning
confidence: 99%
“…associated with an increased likelihood of SARS-CoV-2 spread. 16 The role of such exposures as well as the role of the presence of children in the household have not been investigated as risk factors for severe COVID-19like illness (ie, hospitalisation). We found that the risk of hospitalisation due to COVID-19 was higher among participants who had (vs those who did not have) children in the home, with an adjusted OR (aOR) of hospitalisation of 10.5 (95% CI: 5.7 to 19.1) among study participants living in multiunit dwellings and 2.2 (95% CI: 1.2 to 6.5) among those living in single-unit dwellings.…”
Section: Covid-19 Symptoms and Care Outcomesmentioning
confidence: 99%
“…The results presented here suggest that communities in which people interact more densely from the perspective of disease transmission (e.g., downtowns) may similarly act as contagion reservoirs which may prolong the duration of outbreaks and potentially create secondary reinfection waves. However, the factors that lead to a higher density of social interactions in one community, for example, household size 24,25 or employment in the service industry or essential worker status 26 , can often be the result of long term structural inequalities [47][48][49][50] . These factors must be accounted for when attempting to explain causal sources of differences in transmission rates within cities and in planning responses to outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not expect this to hold later in the pandemic, as social distancing and lockdowns disrupt the social networks of cities, specifically to reduce contacts, and this modifies the urban scaling laws. Later in the pandemic, when mitigation measures have been implemented, we expect neighborhood and individual variations in social network size after social distancing [during complete lockdowns this is roughly equivalent to household size, which has been demonstrated to be a significant risk factor for COVID-19 transmission 24,25 ], face covering compliance, and availability of work-from-home 26 to influence transmission rates. In addition, neighborhood and individual differences in co-morbidities are likely relevant to understanding the variance in morbidity and mortality outcomes within cities, but are not accounted for here where the focus is on transmission rates.…”
Section: Introductionmentioning
confidence: 99%